2014
DOI: 10.1124/dmd.113.056531
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Metabolism, and Excretion of [14C]Axitinib, a Vascular Endothelial Growth Factor Receptor Tyrosine Kinase Inhibitor, in Humans

Abstract: The disposition of a single oral dose of 5 mg (100 mCi) of [ 14 C]axitinib was investigated in fasted healthy human subjects (N = 8). Axitinib was rapidly absorbed, with a median plasma T max of 2.2 hours and a geometric mean C max and half-life of 29.2 ng/ml and 10.6 hours, respectively. The plasma total radioactivity-time profile was similar to that of axitinib but the AUC was greater, suggesting the presence of metabolites. The major metabolites in human plasma (0-12 hours), identified as axitinib N-glucuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…Chemical inhibition studies suggested minor roles for CYP2C19 and CYP2D6; however, when using recombinant enzymes only CYP2C19 was shown to form metabolites at a CL int contribution greater than 0.3%. Conversely, a role for CYP1A2 could not be shown through inhibition by furafylline in HLMs, but studies using recombinant enzymes have demonstrated that CYP1A2 was the only enzyme that formed M12a, an in vivo metabolite of axitinib in humans (Smith et al, 2014). Axitinib metabolism in HLMs was inhibited by ,10%, each by montelukast and sulfaphenazole, selective inhibitors for CYP2C8 and CYP2C9, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Chemical inhibition studies suggested minor roles for CYP2C19 and CYP2D6; however, when using recombinant enzymes only CYP2C19 was shown to form metabolites at a CL int contribution greater than 0.3%. Conversely, a role for CYP1A2 could not be shown through inhibition by furafylline in HLMs, but studies using recombinant enzymes have demonstrated that CYP1A2 was the only enzyme that formed M12a, an in vivo metabolite of axitinib in humans (Smith et al, 2014). Axitinib metabolism in HLMs was inhibited by ,10%, each by montelukast and sulfaphenazole, selective inhibitors for CYP2C8 and CYP2C9, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These glucuronides were identified as Glu1, Glu2, and Glu3 (Supplemental Table 3). Glu2 was subsequently identified as axitinib N-glucuronide (M7), a major circulating metabolite in humans (Smith et al, 2014). Therefore, M7 was prepared biosynthetically as an authentic standard for further in vitro evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations